2018
DOI: 10.3389/fncom.2018.00080
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Combining Neuronal Feedback and Feed-Forward Control for Robustness in Step Down Perturbations of Simulated Human Walking Depends on the Muscle Function

Abstract: It is often assumed that the spinal control of human locomotion combines feed-forward central pattern generation with sensory feedback via muscle reflexes. However, the actual contribution of each component to the generation and stabilization of gait is not well understood, as direct experimental evidence for either is difficult to obtain. We here investigate the relative contribution of the two components to gait stability in a simulation model of human walking. Specifically, we hypothesize that a simple line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Perturbations seem to be better compensated in the healthy comparison group on a longer time scale based on trunk movements and on a shorter time scale (almost instantaneously) according to the foot kinematics. Probably, some mechanisms to compensate perturbations occur nearly instantly or in a short period within the lower extremities, for example, when preparing the leg for ground contact by an adequate adjustment of muscle (pre-) activation [32,33] or joint stiffness [34]. On the other hand, some trunk-based mechanisms might need more time to affect stability, e.g., recovery movements from perturbations due to armswing [35] or directing the ground reaction forces to an intersection point above the center of mass [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations seem to be better compensated in the healthy comparison group on a longer time scale based on trunk movements and on a shorter time scale (almost instantaneously) according to the foot kinematics. Probably, some mechanisms to compensate perturbations occur nearly instantly or in a short period within the lower extremities, for example, when preparing the leg for ground contact by an adequate adjustment of muscle (pre-) activation [32,33] or joint stiffness [34]. On the other hand, some trunk-based mechanisms might need more time to affect stability, e.g., recovery movements from perturbations due to armswing [35] or directing the ground reaction forces to an intersection point above the center of mass [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used simulation to study walking balance using a variety of approaches [14,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Simplified biped models have been used to study how modulating push-off [28,32] and joint speed [22] can help stabilize walking.…”
Section: Introductionmentioning
confidence: 99%
“…Simplified biped models have been used to study how modulating push-off [28, 32] and joint speed [22] can help stabilize walking. Several studies have simulated how humans maintain walking balance using models of muscle-reflex through feedback control [26, 27, 33, 34] based on the model of Geyer and Herr (2010) [36], and others have incorporated feed-forward control strategies to model the contribution of central pattern generators to walking balance [21, 23, 30]. Three-dimensional musculoskeletal simulations have revealed the contributions of muscles to medio-lateral ground reaction forces [14, 24] and foot placement strategies after perturbation [29, 35].…”
Section: Introductionmentioning
confidence: 99%
“…Initially it was claimed that this type of feedback was sufficient to evoke locomotion, even in the absence of a CPG, but more recent work showed that the addition of CPG to this model greatly improved its performance (Dzeladini, van den Kieboom, & Ijspeert, 2014;Haeufle, Schmortte, Geyer, Müller, & Schmitt, 2018). More recently, a combination of CPGs with bioinspired sensory feedback was employed to make a complex 3D biped robot (COMAN) walk stably with a straightforward speed control (Van der Noot, Ijspeert, & Ronsse, 2018a; Van der Noot, Ijspeert, & Ronsse, 2018b).…”
Section: Simulations and Roboticsmentioning
confidence: 99%